Investment in ICT in Developing Countries: the effect of FDI: Evidences from Sultanate of Oman - Alraja, Mansour Naser; Hammami, Samir; Al Samman, Hazem Mohammed (International Journal of Economics and Financial Issues, 2016)
Foreign direct investment (FDI) is a crucial tool developing the economy of any country if it is employed in a proper manner. Moreover, foreign direct investment has many effects; and one of them is thriving the information and communication technology (ICT) sector as a pivotal sector which includes four sub-sectors according to the World Bank (ICT Service Exports, ICT Goods Imports, High-Technology Exports and ICT Goods Exports). Hence, the aim of this paper is to identify the influence of foreign direct investment in thriving the sub-sectors of information and communication technology, as one of the drivers to develop the economy. To accomplish this purpose the statistical data on direct foreign investment and exports and imports of information and communication technology about Sultanate of Oman were collected from 2000-2014 published by the World Bank. descriptive statistics and Simple regression model were used to analyze the collected data and test the hypotheses of the study. The findings show that the planning for foreign direct investment is ad-hoc, therefore there should be a obvious view of how to exploit foreign direct investment in economy development, especially in transferring of information and communication technology. The paper contributed to the literature by being the first study that attempted to interpret the role of foreign direct investment on exports and imports of information and communication technology in Sultanate of Oman. Keywords: Foreign direct investment (FDI), ICT, High-Technology Exports, ICT Goods, ICT Service Exports, ICT Goods Imports, Oman. JEL Classifications: F14, N8